2021
DOI: 10.1128/mra.01043-21
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequences of Bacteriophages Kaya, Guyu, Kopi, and TehO, Which Target Clinical Strains of Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa is a major public health concern, as drug-resistant strains increase mortality in hospital-acquired infections. We report the isolation and complete genome sequences of four lytic bacteriophages that target clinical multidrug-resistant P. aeruginosa strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…S1). Standard nucleotide BLAST demonstrated that phipa2, phipa4, and phipa10 closely resemble that of the P. aeruginosa phage vB_Pae_QDWS (coverage 94% and identity 96.81%) ( 22 ), phage Kopi (coverage 93% and identity 96.60%) ( 23 ), and phage YS35 (coverage 96% and identity 96.76%) ( 24 ), respectively. The schematic maps of the phage genomes are listed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S1). Standard nucleotide BLAST demonstrated that phipa2, phipa4, and phipa10 closely resemble that of the P. aeruginosa phage vB_Pae_QDWS (coverage 94% and identity 96.81%) ( 22 ), phage Kopi (coverage 93% and identity 96.60%) ( 23 ), and phage YS35 (coverage 96% and identity 96.76%) ( 24 ), respectively. The schematic maps of the phage genomes are listed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…From the previous studies, the isolate was found to be multi-drug resistant (MDR) and cause bacteremia in mice [ 16 ]. For the treatment, two previously characterized bacteriophages were used which include Pseudomonas phage AP025 and Pseudomonas phage AP006 [ 22 ]. The characterized Pseudomonas phage AP025 ( Myoviridae ) had infectivity of 39% and Pseudomonas phage AP006 ( Siphoviridae ) with 30% infectivity against 51 P. aeruginosa tested.…”
Section: Methodsmentioning
confidence: 99%
“…Phages for therapy should be strictly virulent (also known as lytic), as studies have shown that prophages (genome-embedded phages with a lysogenic cycle) can alter the characteristics of a host and in some cases, increase virulence, not only in P. aeruginosa but also in other pathogens [ 19 21 ]. Many Pseudomonas phages with potential for clinical use have been reported [ 22 24 ], however, the majority of previously published studies on phage therapy focused mainly on wound infections [ 25 , 26 ]. Our study describes the use of phages in bloodstream infections caused by the pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…no. MZ927746) with 40% query coverage sharing 93.74% to 96.68% identity ( Clark et al, 2019 ; Loh et al, 2021 ). Comparative genomics of NR08 phage with ten Xoophages reported by Kovács et al (2019) (Accession no.…”
Section: Discussionmentioning
confidence: 99%